GIAC security essentials (GSEC) - Lowrie, Daniel; Dennison, Justin (Packt Publishing, 2024)
The course begins with a solid foundation in Access Control and Password Management, setting the stage for a deep dive into the intricacies of cybersecurity. It progresses into exploring Active Defense mechanisms and the development of effective Contingency Plans, ensuring you're prepared for any security incident. The journey continues with an exploration of Critical Controls, Basic and Advanced Cryptography, ensuring a well-rounded understanding of key security principles. The course focuses on laying out a Defensible Network Architecture, Endpoint Security, and enforcing Windows and Linux security, providing a detailed look at how to secure modern operating systems and their networks. Through practical examples, you'll learn about Incident Handling and Response, IT Risk Management, and the importance of Security Policies and Virtualization for a robust cybersecurity posture. The course wraps up by covering Web Communication Vulnerabilities, Vulnerability Scanning, and Penetration Testing techniques, equipping you with the skills to identify and mitigate potential threats effectively.
Online resource; title from title details screen (O'Reilly, viewed March 19, 2024)
Keywords: Computer security; Penetration testing (Computer security); Sécurité informatique; Tests d'intrusion; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet